Fundamentos técnicos tácticos del futbol y la inteligencia emocional en niños - Valdiviezo Remache, Nicolas Mateo (2024)
This research work entitled "Technical and Tactical Foundations of Soccer and Emotional Intelligence in Children" aims to analyze the impact of soccer's technical and tactical foundations on the emotional intelligence of children from the Liga de Quito school in Riobamba. This study applies an investigative approach to a population of 10 students aged 11 years. An observation guide of soccer's technical and tactical qualities and the MESQUITE scale were used as research methods, offering promising perspectives for improving physical capacity. The results obtained in this study provide a solid foundation for developing effective and tailored training programs, significantly enhancing this population's performance and overall well-being.